Rejecting Standard Care: Vitamin K Prophylaxis for Newborns and Parent Choice. Issue 5 (September 2015) - Bauer, Jill A.
Abstract : Parental refusal of vitamin K administration for newborns after birth is on the rise. How can nurses provide adequate information to assist parents in making a truly informed choice about vitamin K so risk of unnecessary harm to babies can be minimized?